PENGARUH RASIO BIAYA OPERASIONAL PENDAPATAN OPERASIONAL (BOPO) DAN NON PERFORMING FINANCING (NPF) TERHADAP NET OPERATING MARGIN (NOM) PADA BANK UMUM SYARIAH YANG TERDAFTAR DI OTORITAS JASA KEUANGAN (OJK) - Yulientinah, Dewi Selviani; Khatami, Raihani Nurjannah (LAND JOURNAL, 2024)
The Financial Services Authority is a state administration tasked with administering a system of regulation and supervision of all activities in the financial sector, such as the banking sector, capital market and non-bank financial services sector, such as insurance, pension funds, financing institutions and others. The phenomenon of a decrease in the net operating margin of Islamic banks attracted the author's interest to investigate further. This purpose of this study is to determine the effect of operating expense on operating revenue ratio (BOPO) and non performing financing (NPF) on the net operating margin (NOM) of Islamic Commercial Banks (BUS) registered on the OJK, either partially or simultaneously. This study uses quantitative methods with secondary data in the form of financial statements. The population are 12 BUS, but the sample used are only 6 BUS for 5 years with purposive sampling method. The analytical technique used is data normality test, product moment correlation test, multiple correlation test, multiple regression test, coefficient of determination test, t test and F test. The results of t test indicate that BOPO has a significant effect partially on NOM, while NPF has no significant effect partially on NOM. The results of the F test show that the BOPO and NPF have a significant effect simultaneously on NOM with a percentage coefficient of determination is 69.8%.